2015
DOI: 10.3390/antibiotics4030358
|View full text |Cite
|
Sign up to set email alerts
|

Short, Synthetic Cationic Peptides Have Antibacterial Activity against Mycobacterium smegmatis by Forming Pores in Membrane and Synergizing with Antibiotics

Abstract: Multicellular organisms are constantly exposed to a multitude of pathogenic microbes. Infection is inhibited in vivo by the innate and adaptive immune system. Mycobacterium species have emerged that are resistant to most antibiotics. We identified several naturally occurring cationic antimicrobial peptides that were active at low micromolar concentrations against Mycobacterium smegmatis. Human-derived cathelicidin LL-37 is well characterized and studied against M. smegmatis; we compared LL-37 with Chinese cobr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 61 publications
5
43
1
Order By: Relevance
“…In other cases, the second component somehow strengthens the action of the first component by facilitating access to the molecular target. This is how antibacterial peptides work, which cause permeabilization of the membrane, which in turn causes the release of antibiotics into the periplasm and cytoplasm of bacterial cells [42,[51][52][53][54][55][56]. It is also known that Staphylococci have an efflux pump, which determines drug resistance to a large extent because it is responsible for removing from cells various types of substances, which are unnecessary for metabolism or harmful to cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, the second component somehow strengthens the action of the first component by facilitating access to the molecular target. This is how antibacterial peptides work, which cause permeabilization of the membrane, which in turn causes the release of antibiotics into the periplasm and cytoplasm of bacterial cells [42,[51][52][53][54][55][56]. It is also known that Staphylococci have an efflux pump, which determines drug resistance to a large extent because it is responsible for removing from cells various types of substances, which are unnecessary for metabolism or harmful to cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on synthetic forms of bactenecin reported the increased efficiency of this peptide with changes in its sequence and structure (25,26). The MIC test with E. coli (ATCC 25922) was conducted here for each peptide (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…• Na-CATH: this CATH from the venom gland of the Chinese cobra N. atra [76] also demonstrated powerful, salt-resistant, antimicrobial activity against Gram-positive and Gram-negative bacteria, including Francisella novicida (the non-virulent strain in humans related to Francisella tularensis, the causative agent of tularemia) [98], E.coli, Aggregatibacter actinomycetemcomitans, Bacillus cereus [99], P. aeruginosa [100], and S. aureus [101] at low concentrations (EC 50 < 3 µg/mL). Na-CATH is also active against Mycobacterium smegmatis [102], Burkholderia thailandensis (closely related to B. pseudomallei, the causative agent of melioidosis) [103] and Bacillus anthracis (anthrax) [104]. The last two strains are of particular relevance due to their potential use as biological weapons.…”
Section: Sourcementioning
confidence: 99%
“…In addition, Na-CATH is not only active against planktonic bacteria, but also inhibits S. aureus and B. thailandensis biofilm formation [101,102], while inducing minimal hemolysis (<2% at 100 µg/mL) [99]. However, Na-CATH did not inhibit Pseudomonas biofilm formation [100].…”
Section: Sourcementioning
confidence: 99%